X-ray Computed Microtomography for the Inspection of Flexible Risers - Adriana José da Penha Moreira; O. M. O. Araújo; A. S. Machado; R. T. Lopes; D. F. Oliveira (Brazilian Journal of Radiation Sciences)
The integrity of flexible risers, essential for transporting oil from wells to platforms, is often compromised by residual gases such as CO2 and H2S, which cause fatigue through corrosion. The marine environment, with its bending loads, radial forces, and internal and external pressures, intensifies this process, requiring continuous monitoring and maintenance to prevent the degradation of the metallic layers. Flexible risers are composed of polymeric and metallic barriers, each with specific functions to ensure flexibility and pressure resistance. However, the rupture of wires in the tensile armor layers, often initiated by manufacturing defects, represents a significant failure mechanism. A gap has been identified in current inspection methods, which are intrusive or have limited sensitivity in some regions of the risers. To address this issue, the use of X-ray Computed Microtomography (microCT) is proposed as a non-invasive technique to detect microcracks in the layers of flexible risers. In this study, a section of flexible riser 440 mm in length and 155 mm in diameter was scanned by the Phoenix V|tome|x M/Waygate Technologies microtomograph, which has a 500 W range microfocus tube and a GE PXR250RT detector with a pixel size of 200 µm. Subsequently, the projections were reconstructed, and the images were analyzed in specialized software. The results showed defects along all layers of the riser. The application of microCT to enhance defect detection is suggested, which could contribute to safer and more reliable offshore oil and gas operations.